Femoral offset is underestimated on anteroposterior radiographs of the pelvis but accurately assessed on anteroposterior radiographs of the hip - Merle, Christian; Streit, Marcus R.; Gotterbarm, Tobias (Journal of bone and joint surgery. B, British volume, 2012)
The aim of this retrospective cohort study was to identify any difference in femoral offset as measured on pre-operative anteroposterior (AP) radiographs of the pelvis, AP radiographs of the hip and corresponding CT scans in a consecutive series of 100 patients with primary end-stage osteoarthritis of the hip (43 men and 57 women with a mean age of 61 years (45 to 74) and a mean body mass index of 28 kg/m2 (20 to 45)).Patients were positioned according to a standardised protocol to achieve reproducible projection and all images were calibrated. Inter- and intra-observer reliability was evaluated and agreement between methods was assessed using Bland-Altman plots.In the entire cohort, the mean femoral offset was 39.0 mm (95% confidence interval (CI) 37.4 to 40.6) on radiographs of the pelvis, 44.0 mm (95% CI 42.4 to 45.6) on radiographs of the hip and 44.7 mm (95% CI 43.5 to 45.9) on CT scans. AP radiographs of the pelvis underestimated femoral offset by 13% when compared with CT (p < 0.001). No difference in mean femoral offset was seen between AP radiographs of the hip and CT (p = 0.191).Our results suggest that femoral offset is significantly underestimated on AP radiographs of the pelvis but can be reliably and accurately assessed on AP radiographs of the hip in patients with primary end-stage hip osteoarthritis.We, therefore, recommend that additional AP radiographs of the hip are obtained routinely for the pre-operative assessment of femoral offset when templating before total hip replacement.
Gesehen am 30.11.2018